The role of celebrity radio DJs in contemporary radio industry: a case study of Prambors network - Singarimbun, Kartika; Siti Karlinah; Hidayat, Dadang Rahmat; Darwis, Yuliandre (Penerbit Universiti Kebangsaan Malaysia, 2019)
In music radio broadcasts, radio DJs play an important role in the success of broadcast programs. The words and expressions used are very important in building relationships with the listener. As a form of business development, Prambors Radio forms a network that broadcasts homogeneous content simultaneously. For efficiency reason, the company uses national television celebrities as radio DJs for the listeners’ needs. This study uses the commercial radio station Prambors Radio Network broadcast in nine cities in Indonesia as an exemplar for understanding the commodity process of radio workers. Using Vincent Mosco's key theories, the commodification of labor, to explain how services and ideas transform into commodities or trade objects, this research argues that Prambors Network uses national celebrity radio DJs not only to broaden the broadcast reached, but also to attract advertisers as well. Celebrity radio DJs, in particular, are leased by the company to the fans and are expected to increase audience number (share) for the benefit of client products. Through qualitative interviews with radio owners, workers, and observations, this research shows that Prambors Network has created a new strategy to build proximity with listeners by utilizing celebrity radio DJs for AC Nielsen radio rating and number of listeners. Their fame is used in all radio promotional materials, both on prime time morning show and promotion of the radio brand itself. The results of the exploitation of national celebrities as radio DJs are marginalization of local human resources and the broadcasting of Jakarta-centric information.